2002
DOI: 10.1246/cl.2003.52
|View full text |Cite
|
Sign up to set email alerts
|

Novel Utilization of Impedance Measurement for Electrochemical Biosensing Aiming at Elimination of Influence by Interference Materials

Abstract: Application of the ac impedance technique to the electrochemical glucose sensing allowed determination of glucose concentration without influence of a serious interference material, ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Figure 11 shows the Nyquist plots taken by a glassy carbon electrode polarized at 0.36 V vs. Ag/AgCl in the electrolyte solution containing 30 mmol dm À3 GOx, 0.2 mmol dm À3 ferrocenecarboxylic acid and glucose in its concentration from 0 to 10 mmol dm À3 . 37 A straight line is seen for the electrolyte solution in the absence of glucose, whereas the line tends to draw a semicircle by addition of glucose. Its diameter decreases with an increase in glucose concentration.…”
Section: ç Electrochemical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11 shows the Nyquist plots taken by a glassy carbon electrode polarized at 0.36 V vs. Ag/AgCl in the electrolyte solution containing 30 mmol dm À3 GOx, 0.2 mmol dm À3 ferrocenecarboxylic acid and glucose in its concentration from 0 to 10 mmol dm À3 . 37 A straight line is seen for the electrolyte solution in the absence of glucose, whereas the line tends to draw a semicircle by addition of glucose. Its diameter decreases with an increase in glucose concentration.…”
Section: ç Electrochemical Techniquesmentioning
confidence: 99%
“…Attempt was made to apply the electrochemical AC impedance technique to the biosensing system for detecting the desired species with high selectivity. 37,38 The experiments were conducted using the electrolyte solution containing enzyme, electron mediator, and substrate. It was the key point to choose an electron mediator having redox potential that was more positive than oxidation potential of the interference substances, as shown in Figure 10.…”
Section: ç Electrochemical Techniquesmentioning
confidence: 99%
“…On the other hand, if IwaveA is obtained from an experimental result, Z may be considered in Eq. (9). From the Eqs.…”
Section: Wavelet Transformation Of Simulated Sigmoidal Wavesmentioning
confidence: 99%
“…In this case, if the cost of the membrane is expensive, the price of one biosensor tip may be very expensive. 8 Kuwabata et al [9][10][11] applied electrochemical impedance spectroscopy (EIS) to electrochemical glucose sensing without any selective permeable membranes. EIS is one of the nondestructive methods for measuring the current response to the application of sinusoidal AC voltage at various frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] In our previous paper, we have reported that electrochemical determination of glucose using GOx and ferrocenecarboxylic acid as an electron mediator can be conducted by using AC impedance measurements. 32 A calibration curve has been drawn by using the reaction impedance obtained from the Nyquist plots and presence of ascorbic acid did not affect the calibration curve. The present paper expands on the previous study.…”
mentioning
confidence: 99%